2006
DOI: 10.1529/biophysj.106.081687
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Modular Proteins Occur in the Extracellular Mucilage of the Motile, Pennate Diatom Phaeodactylum tricornutum

Abstract: This Letter reports on adhesive modular proteins recorded by atomic force microscopy on live cells from the extracellular mucilage secreted from, and deposited around, the motile form of the pennate diatom Phaeodactylum tricornutum. This is the first report of modular proteins and their supramolecular assemblies, called adhesive nanofibers (ANFs), to be found on diatoms that use adhesives not only for substratum adhesion, but as a conduit for cell motility. The permanent adhesive pads secreted by Toxarium undu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 13 publications
2
55
0
1
Order By: Relevance
“…This includes the permanent adhesive pad secreted by the centric diatom Toxarium undulatum [11,12,14] and the temporary adhesive EPS secreted by the motile, pennate diatom Phaeodactylum tricornutum [13]. To date there has been no identification of any protein from the family of structurally homologous proteins that would need to exist in order to explain the observed sawtooth responses of different dimensions found from an increasing number of different natural adhesives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the permanent adhesive pad secreted by the centric diatom Toxarium undulatum [11,12,14] and the temporary adhesive EPS secreted by the motile, pennate diatom Phaeodactylum tricornutum [13]. To date there has been no identification of any protein from the family of structurally homologous proteins that would need to exist in order to explain the observed sawtooth responses of different dimensions found from an increasing number of different natural adhesives.…”
Section: Resultsmentioning
confidence: 99%
“…EPS is therefore considered to be a complex mixture of structural and functional proteins, glycoproteins, and proteoglycans arranged in a 3-D matrix structure. 466 A. S. Mostaert et al While studies continue to attempt chemical characterization of algal EPS, mainly of diatoms [10,11], recent studies [12][13][14][15] have begun to explore the nanomechanical properties of algal adhesives using the atomic force microscope (AFM) [16]. The AFM is a particularly effective tool for measuring the adhesion of nanoscale volumes of material as it relies upon sensitive laser detection of the deflections of a small cantilever-mounted tip, in response to intermolecular forces between the tip and material of interest.…”
mentioning
confidence: 99%
“…For this, the surface chemistry of the involved particles is critical, and it is not surprising that different algae are different in this respect. It is outside the scope of this paper to make any analysis of the underlying chemistry, but the flocculation of P. tricornutum at a relatively low pH could be due to adhesive proteins at the cell surface (Dugdale et al 2006). The adhesiveness of the surface can to a large degree be altered by the algae themselves (when healthy), and increasing adhesiveness is an active strategy for some species in order to, e.g., attach to surfaces (Hoagland et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…obliquus at high pH was studied. The reason behind choosing these species was that adhesive proteins in P. tricornutum have been identified (Dugdale et al 2006), and diatoms in general seem to flocculate at high pH (Knuckey et al 2006). In contrast, previous studies have suggested that S. obliquus does not flocculate very easily at high pH (Lavoie and de la Noüe 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms responsible for biofouling not only differ in adhesive strength depending on the surface they are exposed to but also in terms of the difference in adhesive strength between species (Holland et al, 2004). The isolate Pt 1.8.6 has been used in nearly all of the P. tricornutum studies described in the literature (Borowitzka & Volcani, 1978;Scala et al, 2002;Montsant et al, 2005;Dugdale et al, 2006). It is from this isolate that the genome has been sequenced and the EST libraries created (Montsant et al, 2005).…”
Section: Discussionmentioning
confidence: 99%